P5-S4.07 SMS reminders increase re-testing for repeat chlamydial infection in heterosexuals at a sexual health clinic. (10th July 2011) - Guy, R; Wand, H; Read, P; Kenigsberg, A; Knight, V; McNulty, A
Abstract : Background: Repeat infection with Chlamydia trachomatis following treatment is common. If left untreated it can lead to onward transmission and in females it increases the risk of pelvic inflammatory disease by fourfold. In late 2008, Sydney Sexual Health Centre implemented a reminder system using short message service (SMS) to improve re-testing rates following treatment of chlamydial infection. Clinicians were advised to set up SMS reminders to be sent out at 3 months after the visit. Methods: We evaluated the impact of this system in its first year of operation using a controlled observation design. Using logistic regression we assessed the association between a SMS reminder and re-testing within 1–4 months of chlamydia infection in Jan–August 2009 among all heterosexuals. The comparison group was heterosexuals diagnosed with chlamydia who received a brief recommendation to re-test in the same time period. Results: There were 230 heterosexuals diagnosed with chlamydial infection in the study period; 128 females (median age=24 years) and 112 males (median age=26 years). Of these, 47% were sent a SMS reminder (SMS group), and 53% received a brief recommendation (comparison group). The re-testing rate within 1–4 months of chlamydial infection was 58% in the SMS group, compared to 42% in the comparison group, OR=1.9, 95% CI 1.1 to 3.2, p=0=002. In females, the chlamydia re-testing rate within 1–4 months of chlamydial infection was 57% in the SMS group, compared to 40% in the comparison group, OR=2.0, 95% CI 1.0 to 4.0, p=0.05. In males, the chlamydia re-testing rate within 1–4 months of chlamydial infection was 59% in the SMS group, compared to 45% in the comparison group, OR=1.7, 95% CI 0.8 to 3.8, p=0.165. Conclusion: This low cost system substantially increased re-testing rates after chlamydia infection in heterosexuals at a large sexual health clinic. The clinic now plans to implement electronic prompts to remind clinicians to offer SMS reminders to all patients diagnosed with chlamydia.